A Comprehensive Survey of 5G Network Architecture: Techniques, Protocols, and Performance Metrics - Ranjbar, Obaidullah; Aziz Rastagari, Mohammad; Azimi, Sanayee; Danish, Jawad (Gameology and Multimedia Expert, 2025)
This study examines the current state and readiness of 5G network deployment among major telecom operators in Afghanistan, including Roshan, Afghan Wireless Communication Company (AWCC), and ATOMA Telecom. The purpose is to evaluate the architecture, protocols, and performance metrics related to 5G implementation, alongside the challenges faced by the industry in this transitional phase. Using a quantitative survey methodology, data were collected from 50 technical professionals involved in network planning and management. The survey explored infrastructure types in use, stages of 5G planning, familiarity with advanced 5G technologies, and perceived barriers to deployment. Results indicate that while 4G/LTE and 3G remain dominant infrastructures, only a small fraction of organizations have begun 5G trials or deployments. Key obstacles include high infrastructure costs, regulatory issues, spectrum availability, and limited skilled workforce. Additionally, adoption of enabling technologies such as Network Function Virtualization and Software-Defined Networking is emerging but not yet widespread. Overall, the findings highlight that Afghan telecom operators are in the early stages of 5G readiness, requiring significant investment and regulatory support to accelerate deployment. This research contributes valuable insights for policymakers and industry stakeholders aiming to enhance Afghanistan’s 5G ecosystem.